Healthcare Resource Use and Costs of Localized Prostate Cancer Patients in Finland - Murtola, Teemu J.; Hakkarainen, Tuukka; Lahelma, Mari; Pennanen, Paula; Leskelä, Riikka-Leena; Pietilä, Mika; Hervonen, Petteri; Kääriäinen, Okko-Sakari; Minn, Heikki; Nykopp, Timo K.; Ronkainen, Hanna; Ettala, Otto; et al. (Elsevier BV, 2026)
Background
Prostate cancer is the most prevalent cancer among men in Finland, causing significant healthcare costs. Understanding the economic burden of various treatment pathways is vital for optimizing healthcare strategies. This study aimed at estimating healthcare resource utilization and associated costs for patients with localized prostate cancer (LPC) and locally advanced prostate cancer (LAPC) based on initial treatment decisions in Finland.
Patients and Methods
A retrospective, noninterventional study was conducted using pseudonymized patient-level data from the 5 University Hospitals and the Social Insurance Institution of Finland. The cohort included 16,212 adults diagnosed with localized prostate cancer (LPC) or locally advanced prostate cancer (LAPC) between 1 July 2010 and 30 June 2021. Patients were categorized into 4 groups: no immediate treatment (NIT), radiotherapy only (RT), radiotherapy combined with androgen deprivation therapy (RT+ADT), and radical prostatectomy (RP). Healthcare resource utilization and costs were analyzed on a per-patient-year basis, considering inpatient admissions, outpatient visits, emergency department visits, and outpatient medication costs.
Results
The first-year costs were highest for RP (€11,766) and RT+ADT (€10,421), reflecting intensive treatment, followed by RT only (€9,014) and no immediate treatment (NIT) (€4,129). Over time, costs decreased for RP and RT+ADT groups. Emergence of metastatic disease significantly increased costs, particularly due to outpatient medication. Costs began rising 1-2 years before metastasis, indicating early health deterioration.
Conclusion
This study highlights significant cost variations across different treatment pathways for prostate cancer in Finland and underscores the economic impact of metastatic disease. Early detection and effective management are essential for cost containment.